2008
DOI: 10.1248/cpb.56.185
|View full text |Cite
|
Sign up to set email alerts
|

Simple and Rapid UV Spectrophotometry of Caffeine in Tea Coupled with Sample Pre-treatment Using a Cartridge Column Filled with Polyvinylpolypyrrolidone (PVPP)

Abstract: We have applied a sample pre-treatment method with a cartridge column filled with polyvinylpolypyrrolidone (PVPP) to the effective removal of polyphenols and simple UV spectrophotometry of caffeine in tea. The absorption maximum length (l l max ) for caffeine was close to those for tea catechins in aqueous 1% acetic acid; therefore, the UV spectrum of a non-treated green tea sample had a large absorption wave. In contrast, the absorbance of the green tea sample was gradually reduced by PVPP cartridge treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 23 publications
0
8
0
2
Order By: Relevance
“…Thus, would a single chemical or even a combination of chemicals have similar activities of a whole green tea extract that contains many different compounds acting in a additive or synergistic manner? The two compounds, EGCG and caffeine, were chosen because 1) they are the most abundant chemicals found in green tea (Song et al 2003, CafÞn et al 2004; 2) they both have been shown to inhibit the detrimental effects of UVB radiation in mammals (Lu et al 2000(Lu et al , 2007Katiyar 2003;Conney et al 2008;Varma et al 2008); 3) they have antioxidant activities (Devasagayam et al 1996, Katiyar et al 2001, Choi et al 2005, Karori et al 2007); 4) their absorbance maxima is in the UVB portion of the spectrum (Mittai et al 2003, CafÞn et al 2004, Yamauchi et al 2008; 5) they have been found to inhibit UVB-induced damage (Lu et al 2000, Katiyar 2003, Varma et al 2008); and 6) they occur in green tea, black tea, cocoa, and coffee (Table 3). …”
Section: Discussionmentioning
confidence: 99%
“…Thus, would a single chemical or even a combination of chemicals have similar activities of a whole green tea extract that contains many different compounds acting in a additive or synergistic manner? The two compounds, EGCG and caffeine, were chosen because 1) they are the most abundant chemicals found in green tea (Song et al 2003, CafÞn et al 2004; 2) they both have been shown to inhibit the detrimental effects of UVB radiation in mammals (Lu et al 2000(Lu et al , 2007Katiyar 2003;Conney et al 2008;Varma et al 2008); 3) they have antioxidant activities (Devasagayam et al 1996, Katiyar et al 2001, Choi et al 2005, Karori et al 2007); 4) their absorbance maxima is in the UVB portion of the spectrum (Mittai et al 2003, CafÞn et al 2004, Yamauchi et al 2008; 5) they have been found to inhibit UVB-induced damage (Lu et al 2000, Katiyar 2003, Varma et al 2008); and 6) they occur in green tea, black tea, cocoa, and coffee (Table 3). …”
Section: Discussionmentioning
confidence: 99%
“…Various analytical methods have been used for the determination of ASA and CF such as spectrophotometry [10] , spectrofluorimetry [11] , chromatography [12] and Raman spectroscopy [4] . But these methods suffer many drawbacks such as high cost, time consuming and complicated procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Condensed tannins, phenolic compounds also present in grass cell walls, were effectively removed from beer using PVPP 28. Others have removed phenolic compounds from tea29 and separated humic compounds from aqueous solution30 using PVPP contained in chromatography columns.…”
Section: Resultsmentioning
confidence: 99%